An Optically Transparent Ultrabroadband Microwave Absorber - Senfeng Lai; Yanghui Wu; Xiaobo Zhu; Wenhua Gu; Wen Wu (IEEE Photonics Journal)
An optically transparent ultrabroadband microwave absorber was proposed and experimentally verified, which achieved 23.4-GHz deep absorption bandwidth (absorption >0.8 from 15.6 to 39.0 GHz). What is more, the whole absorber is transparent in the visible light range (transmittance >0.8 from 400 to 1100 nm). The absorber thickness was 1.1 mm only, about 1/10 of the center wavelength (9.23 mm, or 32.5 GHz), and can be further reduced. Further analysis showed that the absorber was insensitive to the polarization angle and dropped only little for incident angles smaller than 30°. In general, this absorber can achieve ultrabroadband low reflection in both visible-light and microwave frequencies, providing a new solution for the design of stealth systems.